Contrastive Semantics in Cross-Linguistic Analysis: A Comprehensive Review and Synthesis of Five Crucial Models - Toan, Ly Ngoc (REiLA : Journal of Research and Innovation in Language, 2025)
This study addresses the pressing need for a unified analytical framework in cross-linguistic semantics by integrating five pivotal models: Natural Semantic Metalanguage (NSM), Conceptual Metaphor Theory (CMT), Frame Semantics (FS), Semantic Field Theory (SFT), and Cognitive Grammar (CG) to examine meaning construction in English and Vietnamese. Although substantial theoretical progress has been made in semantic studies, existing research often remains fragmented, with limited integration across models and minimal application to typologically distinct languages. Employing a mixed-methods design, this study analyzed ten short stories using Wordsmith 8.0 and NVivo 14, capturing both quantitative patterns and qualitative nuances in linguistic structure. The findings reveal not only shared semantic primitives and embodied metaphors but also significant cultural variations in conceptual frameworks, including collectivist and individualist tendencies reflected in frame activation and metaphor usage. These insights contribute to the development of an integrated semantic framework that supports more nuanced cross-linguistic comparisons and highlights the dynamic interplay among cognition, language, and culture. Beyond its theoretical significance, the proposed framework holds practical value for language education, translation practices, and computational linguistics by enabling culturally informed semantic analysis. Ultimately, this research reconceptualizes contrastive semantics as an interdisciplinary and culturally grounded field, offering essential tools for enhancing semantic.